Online Course Curriculum Design for Subject Matter Experts: An Agile Methodology - Luis Rojas; Katrina Sorbello; Cristian Rusu; John W. Castro; Paulina Gonzalez-Martinez; Claudio Alvarez; Fei Luo (IEEE Access)
Curriculum design is a critical component of course development, facilitating the creation of meaningful learning experiences across delivery methods and learner types. Existing curriculum design methodologies often assume that educators possess prior knowledge and experience in curriculum development. However, these frameworks do not account for Subject Matter Experts (SMEs) who, with limited or no curriculum design experience, seek to develop online courses. Furthermore, current methodologies lack a learner-centered process model that is agile and responsive to external changes. With their inherent flexibility and adaptability, Agile methodologies offer potential solutions by allowing for quick adaptation to shifting educational environments. This paper introduces Agile Online Course Curriculum Design (AOCCD). This framework empowers SMEs to create learner-centered online curricula through iterative development cycles incorporating continuous learner feedback. The AOCCD was validated through a mixed-method study in which 12 SMEs applied this approach to develop their online course curricula, assessing its utility and effectiveness. Results demonstrate that AOCCD enables SMEs, regardless of prior curriculum experience, to create well-structured and scaffolded learner-centered courses, addressing the need for structure and responsiveness in online education design.